Insect based bioconversion: Future need of growing population - KUMAR, ANIL; Vishwajeet (Indian Farming, 2022)
Organic waste from houses, restaurants, food processing plants etc is enormous. The waste is often disposed in the open ground which pollutes the environment. Insect-based bioconversion of such waste can be a solution for diverting the pressure of meat production on agricultural lands. Enterprises like aquaculture and poultry are highly dependent on agricultural lands for nutrition. Hence, insect-based food can also be an option to meet their feedstuff demand. Black soldier fly (Hermetia illucens) which is widely present in India can be utilized for bioconversion of waste. Adoption of such enterprise will not only produce valuable animal feed, biodiesel, fertilizers, drugs etc but also provide employment.